Effect of Omega-3 Addition on Sputum Conversion, Body Mass Index, Interleukin-6, and Lymphocyte Monocyte Ratio in the Treatment of Pulmonary Tuberculosis - Ferryansyah Ferryansyah; Mohamad Isa; Juhairina Juhairina; Haryati Haryati; Ali Assagaf; Erna Kusumawardhani (Publikasi Indonesia, 2025)
This research aims to investigate the impact of omega-3 supplementation on sputum conversion, body mass index (BMI), interleukin-6 (IL-6) levels, and lymphocyte-monocyte ratio (LMR) in patients with pulmonary tuberculosis (TB). Tuberculosis is a significant health problem in Indonesia, with high incidence and mortality rates. Omega-3 fatty acids are known to have anti-inflammatory effects and may enhance the immune response, potentially supporting tuberculosis (TB) therapy. The research methods included bacteriological examination of the sputum, measurement of BMI, IL-6 levels, and MLR in patients who received additional Omega-3 compared to the control group. The results are expected to provide an overview of the effectiveness of Omega-3 as a supportive therapy in treating TB, as well as its contribution to improving patients' nutritional status and immune response. This research is expected to serve as a reference for developing more effective and affordable tuberculosis therapies.